Regenerative grazing an innovative approach to restore rangelands and improve pastoralists livelihoods, case studies from Saudi Arabia and Tunisia - Ouled Belgacem, Azaiez; Al Harbi, Meshal; Njeru, Jeremiah Njeru; Louhaichi, Mounir (2024)
The presentation was delivered during the "KSA Principles and Good Practices in Sustainable Rangeland Management for Land Restoration" side event at COP 16 in KSA. It discussed case studies from Saudi Arabia and Tunisia, highlighting the principles and practices of sustainable rangeland management. The presentation emphasized regenerative grazing techniques that involved short-duration, high-stocking density grazing, which could restore degraded ecosystems, enhance biodiversity, and improve soil and vegetation health. The findings showed significant environmental and socioeconomic benefits, including increased forage production and cost savings for local communities. Engaging local stakeholders in management decisions was crucial for the success and acceptance of these practices.